VD_FINDINFO HC / 2014 / 656 vom 26. August 2014 - VD Tribunal cantonal (2014)
RELATIONS PERSONNELLES, PROVISOIRE, SURVEILLANCEEN GÉNÉRAL, VISITE, REJET DE LA DEMANDE | 273 al. 1 CC, 308 al. 1 let. b CPC (CH)